U mobilization and associated U isotope fractionation by sulfur-oxidizing bacteria - Rosendahl, C. D.; Roebbert, Y.; Schippers, A.; Weyer, S. (Frontiers in Microbiology, 2023)
Uranium (U) contamination of the environment causes high risk to health, demanding for effective and sustainable remediation. Bioremediation via microbial reduction of soluble U(VI) is generating high fractions (>50%) of insoluble non-crystalline U(IV) which, however, might be remobilized by sulfur-oxidizing bacteria. In this study, the efficacy of Acidithiobacillus (At.) ferrooxidans and Thiobacillus (T.) denitrificans to mobilize non-crystalline U(IV) and associated U isotope fractionation were investigated. At. ferrooxidans mobilized between 74% and 91% U after one week, and U mobilization was observed for both, living and inactive cells. Contrary to previous observations, no mobilization by T. denitrificans could be observed. Uranium mobilization by At. ferrooxidans did not cause U isotope fractionation suggesting that U isotope ratio determination is unsuitable as a direct proxy for bacterial U remobilization. The similar mobilization capability of active and inactive At. ferrooxidans cells suggests that the mobilization is based on the reaction with the cell biomass. This study raises doubts about the long-term sustainability of in-situ bioremediation measures at U-contaminated sites, especially with regard to non-crystalline U(IV) being the main component of U bioremediation.